2023
DOI: 10.1177/15347354231213613
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Colorectal Cancer Effects of Fucoidan Complex-Based Functional Beverage Through Retarding Proliferation, Cell Cycle and Epithelial–Mesenchymal Transition Signaling Pathways

Chun-Hao Chan,
Yue-Hua Deng,
Bou-Yue Peng
et al.

Abstract: Background: Fucus vesiculosus-derived fucoidan, a multifunctional bioactive polysaccharide sourced from marine organisms, exhibits a wide range of therapeutic properties, including its anti-tumor effects. While previous research has reported on its anti-cancer potential, limited studies have explored its synergistic capabilities when combined with other natural bioactive ingredients. In this current study, we present the development of an integrative functional beverage, denoted as VMW-FC, which is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“… • The chemical structure formula and 3D structure of LH are shown in respectively. Cell proliferation was assessed using MTT and colony formation assays ( Chan et al, 2023 ). CRC cells were exposed to multiple concentrations (0–100 µM) of LH for 24 and 48 h. MTT assay results showed that LH significantly inhibited CRC cells proliferation in a dose and time-dependent manner ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“… • The chemical structure formula and 3D structure of LH are shown in respectively. Cell proliferation was assessed using MTT and colony formation assays ( Chan et al, 2023 ). CRC cells were exposed to multiple concentrations (0–100 µM) of LH for 24 and 48 h. MTT assay results showed that LH significantly inhibited CRC cells proliferation in a dose and time-dependent manner ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%